A case of metallosis mimicking cutaneous malignant melanoma following total elbow arthroplasty - Mio Arima; Takamitsu Matsuzawa; Eiko Hashimoto; Nobuyasu Ochiai; Keisuke Matsusaka; Takashi Inozume (JEADV Clinical Practice, 2023)
Abstract Metallosis manifests as an abnormal dark macroscopic staining of periprosthetic tissues by metallic particles from the prosthesis. This complication is uncommon in non‐weight‐bearing joints such as the elbow. We describe a rare case of metallosis mimicking cutaneous malignant melanoma following total elbow arthroplasty (TEA). A 77‐year‐old Japanese woman presented to our clinic with a black nodule within a blue‐greyish pigmentation on the left elbow. She had undergone a left TEA 8 years before presentation. X‐ray showed an amorphous increased density shadow accompanied by high‐density substances in the periprosthetic tissues, consistent with the features of metallosis. Surgical debridement and prosthetic removal were performed. Histopathological examination of the pigmented skin around the nodule revealed a dense infiltration of histiocytes with brownish to blackish granular particles in the dermis. The black‐stained periprosthetic tissues exhibited many multinucleated giant cells and histiocytes with similar particles. Additionally, analysis of the paraffin sections containing particles and the scanning electron microscope‐energy dispersive X‐ray spectroscopy (SEM‐EDX) revealed that the metal was composed of titanium and aluminium, which were components of the prosthesis. At the patient's first visit to our clinic, cutaneous malignant melanoma was considered as a possible differential diagnosis based on the clinical appearance. To the best of our knowledge, previous cases of metallosis with this clinical presentation have not been reported.